A taxonomic and biogeographic review of the fossil tapirs from Bolivia - Ferrero, Brenda S. (2014)
Fossil remains of South American tapirs are often fragmentary and scarce compared with those of other mammals that entered South America during the "Great American Biotic Interchange". Here, we review and add to the Pleistocene tapir remains from the Tarija Valley (Bolivia), and provide a taxonomic re-evaluation of Tapirus tarijensis. T. tarijensis was a large-sized animal, approximating the size of the living Malaysian T. indicus and the extinct North American T. haysii. The geographical distribution of Pleistocene records of Tapirus in South America indicates that T. tarijensis was the only known species inhabiting the Tarija Valley during this time.